ChemInform Abstract: A Neighboring Group Participation Strategy: Direct and Highly Diastereoselective Synthesis of 2‐Substituted and 2, 2‐Bisubstituted Perhydrofuro[2, 3‐b]pyran Derivatives. Issue 8 (February 2015) - Ma, Xiaofeng; Tang, Qin; Ke, Jun; Zhang, Jichao; Yang, Xinglong; Shen, Xudong; Shao, Huawu
Abstract The stereochemistry of the products is established by extensive NMR experiments and X‐ray analysis of compound (IX).